Design and optimisation of low-profile omnidirectional tag antennas for on-metal radio frequency identification tagging applications - Tan, Jiun Ian (2024)
Conventional dipole and monopole antennas are not able to maintain their omnidirectionality when being conformally mounted on metallic surfaces. In this project, low-profile dipole and monopole antennas are proposed for on-metal tag design to provide good omnidirectional feature in the UHF passband. The proposed dipole antenna is embedded with highly reactive components, which are in the form of T-shaped patches and arc-shaped stubs. Despite having an electrically small in footprint (35 × 35 mm2) and low in profile (6.4 mm). it can exhibit an omnidirectional radiation pattern on a metal plate with a read distance of ~12.4 m in all the azimuthal directions. Following that, the proposed monopole antenna is shunt-fed by a C-shaped feedline to address the inherent drawbacks of a short monopole antenna. Despite having an electrically small in footprint (35 × 35 mm2) and low in profile (3.2 mm). it can exhibit an omnidirectional radiation pattern on a metal plate with a read distance of ~9.2 m in all the azimuthal directions. An equivalent circuit model has been derived for each of the proposed antennas to analyse their impedance characteristics and improve impedance matching. As a result, both the proposed antennas can obtain a power transmission coefficient of ~100%. The performances of the proposed antennas are compared with all the existing low-profile on-metal omnidirectional tag antennas. From the comparative study, it has been proven that the proposed dipole and monopole antennas are much superior in terms of read performance and footprint.